Pengaruh Disiplin Kerja, Motivasi Kerja, Dan Beban Kerja Terhadap Kepuasan Kerja Karyawan PT Schneider Electric Manufacturing Batam - Halimah Vebiola Simamora; Sukati, Inda (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
Employee job satisfaction is an important factor in the success and growth of a company. Work discipline, work motivation and workload factors are included as important elements in improving individual performance in the workplace. This research aims to identify and analyze the relationship between work discipline, work motivation and workload on employee job satisfaction in the context of PT Schneider Electric Manufacturing Batam. The number of samples taken was 105 respondents who were employees of Floor 3 Lot 4 PT. Schneider Electric Manufacturing Batam. The collected data was analyzed using a multiple linear regression model and SPSS version 25 software was used to process the data in data quality testing, classical assumption testing, influence testing and research hypothesis testing. The results of multiple linear regression testing show that work discipline has a 72% influence on employee job satisfaction, work motivation has a 55.5% influence on employee job satisfaction and workload has a 32.3% influence on employee job satisfaction. The coefficient of determination (R2) shows that 48% of employee job satisfaction at PT Schneider Electric Manufacturing Batam can be explained by factors such as work discipline, work motivation and workload. Research from hypothesis testing shows that there is a positive and significant relationship between work discipline, work motivation and workload on job satisfaction.